TRANSFORMATIVE PROFESSIONAL DEVELOPMENT FOR MATHEMATICS TEACHERS - Guillermo Baluyot Bonghanoy; Alben P. Sagpang; Ronnie A. Alejan Jr.; Louie Resti Rellon (Journal on Mathematics Education, 2019)
This paper was an attempt to redesign the current professional development training for Mathematics teachers in the Philippines. Mathematics teachers claimed that most training and seminars they attended ignored their local work context; was routinely and was hardly applicable to their classroom milieu. By utilizing the transformative professional development training, the teachers identified the classroom issues that had confronted them; restructured their useful pedagogical ideas and instructional plans and materials; implemented these in their classrooms; and shared their reflections on the new teaching experiences. Qualitative data were gathered from focus group discussions and key informant interviews. University researchers (3), secondary Mathematics teachers (28), and students (250) from four rural public schools in the Hamiguitan Range participated. The teachers and students revealed that their lack of self and environmental understanding were the prevalent issues that led to critical behavior in Mathematical cognition and learning. By applying the transformative education in the classroom, promising results like better teacher performance, improved students' interest, and maximized student participation were evident. This transformative professional development training adequately responded to the teachers' work needs and was recommended to other areas of learning.